(untitled) (Journal of the College of Basic Education, 2023)
Countless studies have been written on the great importance of poetry, and the privileged and distinguished positionwhich the poet enjoys in different societies, he has placed the poet at the top of the pyramidIn the past, Socrates likened poets to prophets, and Ward Zorth considered every great poet a teacher.Great, poetry for the Arabs is their collection, and I see Jerji Zaidan that the Arabs are in the pre-Islamic era.A fiercely conflicted society, they preferred the poet to the knight, and much was said about the self-inflatedness of thethe poet and his narcissism, pride and sense of superiority, which sometimes lead to his feeling of alienation fromA backward society does not put him in the place he thinks, as much has been said in the impact of decisive poetry.There is no doubt that these attitudes are positive attitudes from poetry.And the poets, and in what follows from the pages of different negative opinions and attitudes, we found them in many of those whoHe wrote in this regard as well, and a statement of the reasons that prompted these opinions.This research is not meant to belittle the importance of poetry and poets. There is no doubt thatHuman production in any field of life is of individual and social importance.He who says poetry is a distinguished creator, and there is no doubt that we are inclined towards poetry and love to listen to it and read it.But turning a blind eye to the other opinion and neglecting it is not objective in anything, just asExaggeration in raising or lowering the status of the poet and poetry may deviate from the description of reality.Correct description, which is what we tend to.Philosophy:“Plato placed poetry in the lowest rank of his republic,” (1) and placed the poet “ina lower rank than the cobbler.” (2) “Plato emphasized in Ion the difference between the poet and the philosopher, includingIt raises the status of the philosopher and lowers that of the poet.” (3) It is known that Plato expelledPoets from his republic, not because they are secondary imitators according to his theory of imitation, but ratherBecause they are far from the truth, they are like the blind who do not see the light, and Dr. Malik alertedThe student pointed out that, according to Plato, imitation does not mean imitation, but rather means “distancing from the truth.”